Homoisocitrate dehydrogenase from Candida albicans: properties, inhibition, and targeting by an antifungal pro‐drug. Issue 2 (17th December 2012) - Gabriel, Iwona; Vetter, Natasha D.; Palmer, David R.J.; Milewska, Maria J.; Wojciechowski, Marek; Milewski, Sławomir
Abstract The LYS12 gene from Candida albicans, coding for homoisocitrate dehydrogenase was cloned and expressed as a His‐tagged protein in Escherichia coli. The purified gene product catalyzes the Mg2+‐ and K+‐dependent oxidative decarboxylation of homoisocitrate to α‐ketoadipate. The recombinant enzyme demonstrates strict specificity for homoisocitrate. SDS‐PAGE of CaHIcDH revealed its molecular mass of 42.6 ± 1 kDa, whereas in size‐exclusion chromatography, the enzyme eluted in a single peak corresponding to a molecular mass of 158 ± 3 kDa. Native electrophoresis showed that CaHIcDH may exist as a monomer and as a tetramer and the latter form is favored by homoisocitrate binding. CaHIcDH is an hysteretic enzyme. The KM values of the purified His‐tagged enzyme for NAD+ and homoisocitrate were 1.09 mM and 73.7 μM, respectively, and kcat was 0.38 s−1. Kinetic parameters determined for the wild‐type CaHIcDH were very similar. The enzyme activity was inhibited by (2R, 3S)‐3‐(p‐carboxybenzyl)malate (CBMA), with IC50 = 3.78 mM. CBMA demonstrated some moderate antifungal activity in minimal media that could be enhanced upon conversion of the enzyme inhibitor into its trimethyl ester derivative (TMCBMA). TMCBMA is the first reported antifungal for which an enzyme of the AAP was identified as a molecular target.